(untitled) (The South East European Journal of Economics and Business, 2024)
Current literature on the privacy paradox in personalised advertising lacks insight into how consumers’ knowledge of the data types used shapes their responses to these ads. Building on privacy calculus theory, theory of reasoned action, and signalling theory, this research explores how consumers’ knowledge of data types in personalised advertising influences their reactions. Multigroup path analysis examines differences in established relationships based on consumers’ data knowledge. The moderating effect of this knowledge in the relationship between perceived invasiveness and purchase intentions is also tested. Findings from a sample of millennials indicate that privacy concerns increase perceived invasiveness. However, multigroup and moderation analyses reveal that perceived invasiveness’ impact on purchase intentions varies with consumers’ data knowledge. Specifically, in the search history group, perceived intrusiveness negatively affects purchase intentions. These results underscore the situation-specific nature of the privacy calculus and assist advertisers in understanding consumer behaviour in response to personalised ads.